A Study on the Impact of Perioperative Pain Care Management on Pain, Comfort, and Defecation of Patients in Anorectal Surgery - Yimei Liao; Jing Jiang; Jin Luo; Wenwu Du; Weiwei Zhao; Yafeng Zhang (Emergency Medicine International)
Purpose. The aim of the study is to explore the impact of perioperative pain care management on patients’ pain, comfort, and defecation in anorectal surgery. Methods. From January to December 2021, 126 patients who underwent anorectal surgery in our department were selected for the study and were randomly divided into a study group and a control group of 63 patients each after consent was obtained from the patients. The control group was given the usual care protocol and the study group was given the perioperative pain care management on top of the usual care. The two groups of patients were compared in terms of postoperative anal pain rating, comfort score, time to first bowel movement and time spent in bowel movement, the Pittsburgh sleep quality index (PSQI) scores at night, related complications, and satisfaction with care. Results. ① Postoperative anal pain was less severe in the study group than in the control group (P<0.05). ② Postoperative comfort scores were higher in the study group than in the control group (P<0.05). ③ The time to first bowel movement and its duration after surgery were shorter in the study group than in the control group (P<0.05). ④ Patients in the study group had lower postoperative night-time PSQI scores than the control group (P<0.05). ⑤ Patients in the study group had a lower rate of postoperative complications than the control group (P<0.05). ⑥ Patients in the study group had higher postoperative care satisfaction scores than the control group (P<0.05). Conclusion. The application of perioperative pain care management to patients undergoing anorectal surgery plays an important role in reducing anal pain, improving treatment comfort, and relieving difficult defecation symptoms, with significant improvement in postoperative sleep quality and reduction in complications. It is worthy of clinical reference and promotion.